2015
DOI: 10.25110/arqsaude.v18i3.2014.5195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência De Sobrepeso E Obesidade De Crianças E Adolescentes No Brasil: Uma Revisão Sistemática

Abstract: HOBOLD, E.; ARRUDA, M. de. Prevalência de sobrepeso e obesidade de crianças e adolescentes no Brasil: uma revisão sistemática. Arq. Cienc. Saúde UNIPAR, Umuarama, v. 18, n. 3, p, 189-197, set/dez. 2014. RESUMO:O objetivo deste estudo foi revisar as pesquisas de prevalência de sobrepeso e obesidade em crianças e adolescentes brasileiros. Foi realizado a busca eletrônica de artigos nas bases de dados Scielo, PubMed, MedLine e LILACS e na Biblioteca Eletrônica Bireme. Para efeito deste estudo, foram selecionadas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
(19 reference statements)
1
3
0
10
Order By: Relevance
“…However, the highest proportion of obese individuals were found in southeastern region (18.2%), being followed by southern (12.1%), Midwest (11%), northern (7.8%), and northeastern (9%). Comparing previously published studies that analyzed prevalence of overall weight excess, overweight and obesity in Brazilian youth [7][8][9] , we could observe a massive increase of obesity in Brazilian children and adolescents of about 150% (e.g., from 4.8% to 11.6%) during the last 28 years. Overweight presented an increase of 11% (e.g., from 15.2% to 17%) while overall weight excess increased 60% (from 16% to 25.4%) ( Figure 3).…”
Section: … Continuesupporting
confidence: 49%
See 1 more Smart Citation
“…However, the highest proportion of obese individuals were found in southeastern region (18.2%), being followed by southern (12.1%), Midwest (11%), northern (7.8%), and northeastern (9%). Comparing previously published studies that analyzed prevalence of overall weight excess, overweight and obesity in Brazilian youth [7][8][9] , we could observe a massive increase of obesity in Brazilian children and adolescents of about 150% (e.g., from 4.8% to 11.6%) during the last 28 years. Overweight presented an increase of 11% (e.g., from 15.2% to 17%) while overall weight excess increased 60% (from 16% to 25.4%) ( Figure 3).…”
Section: … Continuesupporting
confidence: 49%
“…However, evidence about nutritional status of Brazilian children and adolescents are not properly updatep [7][8][9] . The management of an updated national monitoring panel about children and adolescents nutritional status is seem as essential to organize future prevention and treatment plans aiming to tackle obesity 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that the global prevalence of overweight and obesity among adolescents is over 20% (1) . Brazil follows this trend, and the prevalence ranges from 7.4% to 36.5% in the different states with an average of over 20% (2) . At the local level, a study conducted in the city of Natal, Rio Grande do Norte, in 2013, identified a prevalence of 28.8% of overweight or obese adolescents among students of the state education network, as well as an absence of nursing care directed to this clientele in participating Health Units (3) .…”
Section: Introductionmentioning
confidence: 74%
“…We can highlight that adolescents with obesity are more likely to present psychological disorders, especially depression and anxiety (12) . In Brazil, obesity is the most relevant nutritional deviation in the population; between 2003 and 2012, it was present in more than 20% of adolescents (2) .…”
Section: Resultsmentioning
confidence: 99%
“…Em 2007, em revisão sistemática realizada por Araújo et al 7 , observou-se um número expressivo de estudos epidemiológicos com foco no excesso de peso em adolescentes no Brasil, cuja prevalência oscilou de 4% a 31%. Em 2014, Hobold e Arruda 8 sustentaram os achados de Araújo et al 7 ; no entanto, a prevalência de excesso de peso encontrada variou de 7,4% a 36,5%. Curiosamente, em ambas as revisões, houve uma maior concentração de dados das regiões Sul e Sudeste, e poucos estudos com dados das regiões Nordeste e Centro-Oeste foram rastreados 7,8 .…”
Section: Introductionunclassified